Sex Differences Persist in Time to Presentation, Revascularization, and Mortality in Myocardial Infarction Treated With Percutaneous Coronary Intervention. Issue 10 (21st May 2019) - Stehli, Julia; Martin, Catherine; Brennan, Angela; Dinh, Diem T.; Lefkovits, Jeffrey; Zaman, Sarah
Abstract : Background: Timely revascularization with percutaneous coronary intervention (PCI) reduces death following myocardial infarction. We evaluated if a sex gap in symptom‐to‐door (STD), door‐to‐balloon (DTB), and door‐to‐PCI time persists in contemporary patients, and its impact on mortality. Methods and Results: From 2013 to 2016 the Victorian Cardiac Outcomes Registry prospectively recruited 13 451 patients (22.5% female) from 30 centers with ST‐segment–elevation myocardial infarction (STEMI, 47.8%) or non–ST‐segment–elevation myocardial infarction (NSTEMI) (52.2%) who underwent PCI. Adjusted log‐transformed STD and DTB time in the STEMI cohort and STD and door‐to‐PCI time in the NSTEMI cohort were analyzed using linear regression. Logistic regression was used to determine independent predictors of 30‐day mortality. In STEMI patients, women had longer log‐STD time (adjusted geometric mean ratio 1.20, 95% CI 1.12‐1.28, P <0.001), log‐DTB time (adjusted geometric mean ratio 1.12, 95% CI 1.05‐1.20, P =0.001), and 30‐day mortality (9.3% versus 6.5%, P =0.005) than men. Womens' adjusted geometric mean STD and DTB times were 28.8 and 7.7 minutes longer, respectively, than were mens' times. Women with NSTEMI had no difference in adjusted STD, door‐to‐PCI time, or early (<24 hours) versus late revascularization, compared with men. Female sex independently predicted a higher 30‐day mortality (odds ratio 1.67, 95% CI 1.11‐2.49, P =0.01) in STEMI but not in NSTEMI. Conclusions: Women with STEMI have significant delays in presentation and revascularization with a higher 30‐day mortality compared with men. The delay in STD time was 4‐fold the delay in DTB time. Women with NSTEMI had no delay in presentation or revascularization, with mortality comparable to men. Public awareness campaigns are needed to address women's recognition and early action for STEMI. Abstract : See Editorial Gulati